Gonadal investment of young males in two blenniid fishes with alternative mating tactics - Oliveira, Rui Filipe (2012)
The males of two blenniid species which exhibited alternative life history tactics and matured in their first year of life varied in size distribution within the age class and in behaviour. Salaria pavo were the smaller fish of the age class and behaved as sneaker males whereas Parablennius sanguinolentus parvicornis were the larger fish and behaved as satellites.